COMPARATIVE ANALYSIS OF THE VOLUME OF COMPOUND SENTENCES IN ENGLISH AND UZBEKISTAN - Sattorova Muattar Abduraupovna (PEDAGOGS, 2025)
Abtract. The article provides information on the comparative analysis of the size of compound sentences in English and Uzbek, and is illustrated with theoretical and practical examples.